A virtude como objeto da dialética em Platão. - SANTOS, José Saulo Nogueira dos (2024)
This work investigates how Platonic dialectics intends to overcome the relativism and ambiguity that exist in some conceptions, in force at the time, of virtue and justice, as supported by sophists, poets or conventional morality. With sophistry, problems emerge regarding the possibility of saying the being of things, in the context in which a process of secularization is observed in the polis. If previously Alétheia prevailed as the word of the masters of truth, the spaces for debate that arise with the rise of democracy promise environments in which the logos begins to depend on its own capacity to convince and not on the authority of the speaker. The autonomy of logos, which in the sophists is elevated to its maximum, presents a series of ethical and epistemological problems, including ethical relativism, of which Thrasymachus is an example, creating a context in which ethics is going through a crisis. It is in this context that Plato confronts sophistics, trying to overcome its relativism, searching for an alternative capable of supporting a universalizable ethics, in his investigations into virtue (areté). In his work Republic we can see, through the change of interlocutors, an approach to the different perspectives regarding the virtue of justice, which have their limitations and ambiguities explained by Socrates. The Platonic response, presented in the dialogue with the introduction of new interlocutors from book II of the Republic, also inaugurates a different form of treatment of the problem regarding virtue, which gives rise to the opportunity to present a notion of justice linked to an idea of a tripartite soul to overcome the Thrasymachus thesis. Through bibliographic research of Plato's books, mainly Meno and Republic, as well as different commentators, we will seek to characterize a Platonic response in his strategies to construct an alternative definition of virtue (areté).